Cultural history - Mohsin, K. M. (Khan Mohammad); Ahmed, Sharif Uddin; Asiatic Society of Bangladesh; Cultural Survey of Bangladesh Project (Dhaka : Asiatic Society of Bangladesh, 2007)
Contributed articles published under the Cultural Survey of Bangladesh Project; translated from Bengali.
Includes bibliographical references and index.
Pathways of women empowerment
BDI
Keywords: Bangladesh -- Civilization